PENERAPAN MODEL PEMBELAJARAN BERBASIS PROYEK DENGAN MEDIA VIDEO DALAM PEMBELAJARAN MENULIS TEKS NEGOSIASI. - Maskur Subaweh, Ahmad; Muthmainnah, Fithry; Suciyati (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The author's concern regarding students' writing skills, who face difficulties in writing negotiation texts, and the limitations of teachers in designing varied learning models, motivated this research. This study is entitled "The Implementation of Project-Based Learning Model in Teaching Negotiation Text Writing Using Video Media for Grade X Students of SMK Negeri 2 Indramayu." The objectives of this research are: 1) to test the effectiveness of applying a project-based learning model with video media in improving negotiation text writing skills, and 2) to understand how students engage in learning to write negotiation texts using a project-based learning model with video media. This research employs an experimental method with a pretest-posttest control group design. The research data was based on the population of all tenth-grade students, using purposive sampling, with class X TKJ 2 designated as the experimental class with 30 students, and class X TKJ 3 as the control class with 29 students. Based on statistical calculations using an independent samples t test, the t-count was 3.070 and the t-table was 1.953. So, t-count 3.070 > t-table 1.953, indicating that Ho is rejected and Hi is accepted. Thus, it can be concluded that the project-based learning model using video media is effective for teaching negotiation text writing. Based on the observation data, it is proven that the implementation of the project-based learning model with video media can increase students' activeness in learning to write negotiation texts.